Relationship Marketing In Healthcare Services: A Study on Mindfulness, Relational Dynamics and Outcomes in Healthcare Organizations in the Maldives - Solih, Mohamed (2010)
This chapter aims to provide a global view of relationship marketing thought and the relevance of established relationship marketing constructs to the healthcare service industry as well as the nature of the research to be under taken. Here the research question the study aims to answer is framed. The relevant literature related to relationship marketing is introduced.